2023
DOI: 10.3389/fimmu.2023.1122586
|View full text |Cite
|
Sign up to set email alerts
|

The role of NOD-like receptors in innate immunity

Abstract: The innate immune system in vertebrates and invertebrates relies on conserved receptors and ligands, and pathways that can rapidly initiate the host response against microbial infection and other sources of stress and danger. Research into the family of NOD-like receptors (NLRs) has blossomed over the past two decades, with much being learned about the ligands and conditions that stimulate the NLRs and the outcomes of NLR activation in cells and animals. The NLRs play key roles in diverse functions, ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 130 publications
0
24
0
Order By: Relevance
“…In contrast, the downregulated genes were related to ribosome pathways. Several studies have demonstrated the important roles of these signaling pathways in either innate immunity or COVID-19 progression, including their utility as diagnostic biomarkers and potential treatment strategies [42][43][44][45][46][47][48]. In addition, we found that some TFs were differentially expressed in severe COVID-19.…”
Section: Severe Covid-19-specific Expression Patterns In Neutrophilsmentioning
confidence: 54%
“…In contrast, the downregulated genes were related to ribosome pathways. Several studies have demonstrated the important roles of these signaling pathways in either innate immunity or COVID-19 progression, including their utility as diagnostic biomarkers and potential treatment strategies [42][43][44][45][46][47][48]. In addition, we found that some TFs were differentially expressed in severe COVID-19.…”
Section: Severe Covid-19-specific Expression Patterns In Neutrophilsmentioning
confidence: 54%
“…Considering that ethanol can activate the NLRP3 inflammasome in astroglial cells and the cerebral cortices of mice (Alfonso-Loeches et al, 2014, 2016, we therefore wondered if an intravenous injection of MSC-EVs was also capable of decreasing the activation of the NLRP3 inflammasome pathway in the hippocampus of ethanol-treated adolescent mice. To answer this question, we first evaluated the components of the NLRP3 inflammasome complex, which requires the adaptor protein ASC and the caspase-1 to activate cytokine release (Almeida-da-Silva et al, 2023). Considering that several inflammatory molecules, such as caspase-11/4, TLR4 or IRAK1 may activate the NLRP3/caspase-1 complex (Kelley et al, 2019;Zheng et al, 2020), we then evaluated the gene expression of these genes (Fig.…”
Section: Msc-evs Restore the Activation Of The Nlrp3 Inflammasome Pat...mentioning
confidence: 99%
“…Several members in the NLRs family have been identified, such as NLRP1 (pyrin domain-containing 1), NLRP3, NLRC4 (caspase recruitment domain-containing 4), and AIM2 (a member of the PYHIN protein family). Activation of NLRs are capable of forming inflammasomes or multiprotein complexes that activate caspase-1, leading to the processing and secretion of pro-inflammatory cytokines interleukin-1β (IL-1β) and IL-18 (Almeida-da-Silva et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal NLRs (also known as NOD-Like Receptors) are only distantly related to those in plants (6, 7), but they are also essential for immunity. Some act as pathogen sensors or transcription factors (8), others are components or modulators of inflammasomes, large protein complexes that are assembled within cells as part of the response to biological or chemical danger (8). Most knowledge about animal NLRs comes from studies of humans and rodents, but their NLR repertoires (20-30 genes) are smaller than those of many other species (911).…”
Section: Introductionmentioning
confidence: 99%